Barriers and facilitators for the sexual and reproductive health and rights of young people in refugee contexts globally: A scoping review. - Veronika Tirado; Josephine Chu; Claudia Hanson; Anna Mia Ekström; Anna Kågesten (PLoS ONE)
Background The need to address sexual and reproductive health and rights (SRHR) in humanitarian settings is more urgent than ever, especially among young refugees. We conducted a scoping review to identify and synthesise the literature on perceived barriers and facilitators to SRHR among young refugees and interventions created to address their needs. Methods We searched three databases (PubMed, Global Health and POPLINE) for peer-reviewed and grey literature published in English between January 2008 and June 2018 that reported on SRHR barriers, facilitators and interventions for young refugees aged 10 to 24 years. We extracted data using standardised templates and assessed the quality of studies according to study design. Data were charted using qualitative content analysis and organised in line with a socio-ecological framework (individual, social and community, institutional and health system, and structural). Findings We screened 1,169 records and included 30 publications (qualitative, quantitative, and mixed methods) across 22 countries; 15 were peer-reviewed articles and 15 were from the grey literature. Twenty-two publications reported on young people in refugee camps or alternatives to camps (e.g. sustainable settlements), and eight referred to young refugees who had been resettled to a third country. We identified 19 sub-categories for barriers and 14 for facilitators at the individual, social and community, institutional and health system, and structural levels. No publications discussed the SRHR challenges faced by young homosexual, bisexual, transgender or queer refugees, or those living with HIV. Nine publications described interventions, which tended to focus on the provision of SRHR services and information, and the training of peers, parents, religious leaders and/or service providers. Conclusions Findings highlight that while young refugees experience similar barriers to SRHR as other young people, many of these barriers are exacerbated by the refugee context. The limited number of publications and evidence on interventions underlines the immediate need to invest in and evaluate SRHR interventions in refugee contexts.